Analysis of Development of Culinary Tourism Management Model in Case StudyEast Luwu District Based On SIG - Syahrial Manaf (AIBPM Publisher, 2020)
ABSTRACT The rapid development of technology makes human needs for information about tourist attractions require the availability of appropriate information systems, therefore the geographic information system of culinary attractions is developed to help tourists. East Luwu Regency is one of the regencies in South Sulawesi that has the potential of culinary tourism which is said if it is not managed well. For this reason, a website application based on geographic information about restaurants serving typical foods of East Luwu Regency was created. In this application, you can see the Login list of the distribution of restaurant locations. Keywords: EastLuwu Regency, Website, Traditional Food.